Influence of vapor chamber shape on thermal performance under partial heating for electronic cooling - Öztop, Hakan Fehmi; Varol, Yasin; Tamdogan, Enes; Parlak, Murat; Senocak, Safak Melih; Cosanay, Hakan (Pergamon-Elsevier Science Ltd, 2025)
Effects of the shape of vapor chamber (VC) under partial heating on thermal performance are experimentally tested in this study for different parameters such as heating area, heating power and temperature value of heaters. Also, effectiveness of vapor chamber is discussed by comparing with copper plate. Partial heating is chosen to simulate the electronical heating of the device. Different vapor chamber types are tested as square VC 56 x 56 mm2, rectangular VC 106 x 70 mm2, square VC 90 x 90 mm2 and circular VC. Thermal resistance is calculated and temperature values are measured from the surface of the VC under different heating area. It is observed that the thermal performance of the vapor chamber is significantly higher than that of the copper plate for all types of VC. Higher thermal resistance is observed when a circular vapor chamber is used with a smaller heater diameter. Thermal resistance value is almost 400 % higher between the lowest and highest value of heater area.
Keywords: Circular vapor chamber; Thermal performance; Heater; Heat transfer; Electronic cooling